Correcting heat‐induced chemical shift distortions in proton resonance frequency‐shift thermometry. Issue 1 (24th August 2015) - Gaur, Pooja; Partanen, Ari; Werner, Beat; Ghanouni, Pejman; Bitton, Rachelle; Butts Pauly, Kim; Grissom, William A
Abstract : Purpose: To reconstruct proton resonance frequency‐shift temperature maps free of chemical shift distortions. Theory and Methods: Tissue heating created by thermal therapies such as focused ultrasound surgery results in a change in proton resonance frequency that causes geometric distortions in the image and calculated temperature maps, in the same manner as other chemical shift and off‐resonance distortions if left uncorrected. We propose an online‐compatible algorithm to correct these distortions in 2DFT and echo‐planar imaging acquisitions, which is based on a k‐space signal model that accounts for proton resonance frequency change‐induced phase shifts both up to and during the readout. The method was evaluated with simulations, gel phantoms, and in vivo temperature maps from brain, soft tissue tumor, and uterine fibroid focused ultrasound surgery treatments. Results: Without chemical shift correction, peak temperature and thermal dose measurements were spatially offset by approximately 1 mm in vivo. Spatial shifts increased as readout bandwidth decreased, as shown by up to 4‐fold greater temperature hot spot asymmetry in uncorrected temperature maps. In most cases, the computation times to correct maps at peak heat were less than 10 ms, without parallelization. Conclusion: Heat‐induced proton resonance frequency changes create chemical shift distortions in temperature maps resulting from MR‐guided focused ultrasound surgery ablations, but the distortions can be corrected using an online‐compatible algorithm. Magn Reson Med 76:172–182, 2016. © 2015 Wiley Periodicals, Inc.